Responsible investing in Kenya: Linking the sophistication of financial markets in Kenya with the possible creation of a sustainability index - Mbugua, Alvin (Research of GSB, 2018)
Kenya has over the last few years witnessed tremendous growth as an emerging market with the GDP growing at 5% and the capital markets having a year on year growth of 19%. Despite the growth and sophistication of the financial markets, a host of hurdles have kept Kenya off the mainstream Responsible Investing agenda. This has resulted in no Socially Responsible Investment (SRI) fund assets and none of the market players being signatories to the United Nations Principles for Responsible Investing (PRI). One of the building blocks to this journey could be introducing a Sustainability Index for listed companies on the Nairobi Securities Exchange (NSE). This would form a basis for integrating Environmental, Social and Governance (ESG) aspects into the private sector and other proponents of the society, including the public sector. This research is thus aimed at linking the growing sophistication of the financial markets in Kenya with the possible creation of a Sustainability Index. In this sense, financial markets are seen to have the power to affect social, economic, and environmental outcomes in which a Sustainability Index could become a good tool in measuring such outcomes. The study adopted a qualitative research design which was used to obtain information based on the key research questions of the study. The research findings suggest that Responsible Investing (RI) is understood within the realm of business ethics and corporate governance. RI is inferred to as a manner of doing business that goes beyond short term financial returns and also takes into account the needs of other stakeholders. ESG aspects identified from the study provide for the requisite issues out of which a Sustainability Index can be developed for measuring the impact of Responsible Investing. Within the framework of a Sustainability Index, it is clear that companies will be made more accountable; redefine their corporate boundaries and through shared value, measure the social and environmental impact of their business model. However, there is still need for increased awareness on RI, stakeholder activism and an improved regulatory framework. Embedding Responsible Investing in Kenya will entail understanding the system of actors, so as to look at opportunities of Creating Shared Value whilst setting this up in the right disclosure model.